2021
DOI: 10.1186/s13073-021-00830-0
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer detection of driver genes at the single-patient resolution

Abstract: Background Identifying the complete repertoire of genes that drive cancer in individual patients is crucial for precision oncology. Most established methods identify driver genes that are recurrently altered across patient cohorts. However, mapping these genes back to patients leaves a sizeable fraction with few or no drivers, hindering our understanding of cancer mechanisms and limiting the choice of therapeutic interventions. Results We present s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…This gap can be solved by complementing cohortlevel approaches with methods that account for all types of alterations and predict drivers in individual samples, for example identifying their network deregulations 64,65,66 or applying machine learning to identify driver alterations 67 . Alternatively, we have shown that systems-level properties capture the main features of cancer drivers, justifying their use for patient-level driver detection 68,69 .…”
Section: Discussionmentioning
confidence: 96%
“…This gap can be solved by complementing cohortlevel approaches with methods that account for all types of alterations and predict drivers in individual samples, for example identifying their network deregulations 64,65,66 or applying machine learning to identify driver alterations 67 . Alternatively, we have shown that systems-level properties capture the main features of cancer drivers, justifying their use for patient-level driver detection 68,69 .…”
Section: Discussionmentioning
confidence: 96%
“…More recently, PANOPLY incorporated clinical features in addition to omics data and applied random forest analysis to identify prioritized treatment given a patient's clinical and molecular profile ( http://kalarikrlab.org/Software/Panoply.html ) and some anecdotal success was reported [ 36 ]. Nulsen et al [ 37 ] developed a one-class support vector machine called sysSVM that was trained on TCGA data to create a pan-cancer detection tool for identifying driver genes at the granularity of single patients ( https://github.com/ciccalab/sysSVM2 ). Computational validation has shown promising results in terms of low false positive rate which is very essential for the clinical utilization but none of the applications has been formally evaluated in clinical contexts.…”
Section: Alteration Interpretationmentioning
confidence: 99%
“…Moreover, integrating different data categories is not necessarily a recent tendency, as papers published in 2009 and 2011 already proposed such strategy. Nonetheless, most of the papers using features from three or more data categories were published from 2015, and those that used four [34,57] or five [54,59] data categories were published mainly in 2020 and 2021, which may indicate a trend for increasing data diversity in newer models.…”
Section: Data Categoriesmentioning
confidence: 99%
“…Davoli et al [23] proposed an entropy-based mutation selection score that reflects the spatial distribution of these features, measuring the preferred occurrence of specific point mutations within a gene, termed 'mutation hotspots'. This measure of positional clustering was further adopted by several papers [29,34,45,48,54,59]. Mutation hotspots were also detected using scores computed by OncoDriveCLUST [26,59,64] and applying density estimates to aggregate closelyspaced missense mutations into peaks and compute mutation fraction inside the highest peak [53].…”
Section: Genomic Variationmentioning
confidence: 99%
See 1 more Smart Citation